Efetividade de dentifrícios clareadores comparados ao clareamento dental caseiro supervisionado - revisão sistemática e metanálise - Pezzini, André Alexandre (2019)
Objective: A systematic review and meta-analysis were performed to evaluate the color change (CC), risk and intensity of tooth sensitivity (TS), gingival irritation (GI) and patient’s satisfaction (PS) comparing whitening dentifrices versus dental bleaching in adult patients of any age made at home. Sources: On 2018 august 7th a comprehensive search was performed in MEDLINE via PubMed, Cochrane Library, Brazilian Library in Dentistry, Latin American and Caribbean Health Sciences Literature database (LILACS) and citation databases, Scopus and Web of Science. IADR abstracts (1990–2018) unpublished and ongoing trials registries, dissertations and theses were also searched. Study selection: After two reviewers remove the duplicates, title and abstract screening, 4 parallel randomized clinical trials (RCTs) studies were included, which compared whitening dentifrices versus at home dental bleaching made in adult patients of any age group. Meta-analysis was conducted for CC in objective scale (ΔE*) and subjective scale (ΔSGU), risk and intensity of TS, risk of GI with Visual Analog Scale (VAS), and PS by random effects model. No significant difference in ΔSGU, risk and intensity of TS, risk of GI and PS was observed (p > 0.05). Conclusion: There was no difference between whitening dentifrices and at home dental bleaching in adult patients. However, this result is probably due to the limited number of studies included in this review, and in this way, we emphasize that the subject should remain under investigation.